Ic paper on elekta Ab - power of proton solutions in radiotherapy market - Fernandes, Gonçalo Ermida Rosinha Monteiro (2021)
The following Investment Committee paper focuses on a proposal for a leveraged buyout on Elekta AB, a key player in the global radiotherapy market which sells in more than 120 countries. In fact, this paper develops a set of value creation strategies, with special focus on Buy-and-Build, based on company and market analysis, reflecting those strategies in a detailed operating model. Subsequently, a capital structure is suggested by assessing past buyout transactions in the healthcare sector and by leveraging the bank case. Finally, the exit returns are estimated complying with industry threshold and a range of exit strategies are analyzed.